Case report: Infectious mononucleosis with bilateral retinal haemorrhages under myelin oligodendrocyte glycoprotein antibody-associated disease - Li, Yuyu; Sun, Mingming; Wei, Shihui; Xu, Quangang; Zhou, Huanfen (Frontiers in Immunology, 2024)
BackgroundBilateral optic neuritis associated with optic disc swelling is a common feature of myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). However, extensive deep retinal haemorrhages have not been described in the context of MOG-associated optic neuritis. Here, we report a case of infectious mononucleosis with marked binocular peripapillary and perivascular haemorrhages as well as extensive deep retinal haemorrhages in the presence of MOGAD.Case reportA 39-year-old Chinese woman presenting with subacute binocular vision reduction with no light perception was diagnosed with MOGAD. Fundus examination revealed the presence of binocular peripapillary and perivascular haemorrhages as well as extensive deep retinal haemorrhages with severe optic disc swelling greater in the right eye than in the left and dilated and tortuous retinal venules. The patient tested positive for the Epstein–Barr virus (EBV) antigen (595 U/mL) and the EBV capsid antigen (>750 U/mL). She had a fever and right upper quadrant abdominal pain, and a doctor determined splenomegaly 1 week before the onset of orbital pain and decreased vision acuity. Medical history and laboratory tests indicated the presence of concurrent infectious mononucleosis. Other investigational indicators of retinal haemorrhages, including hypertension, diabetes mellitus, vascular disease, systemic lupus erythematosus, metabolic disease, and renal or liver dysfunction, were absent.DiscussionThis case suggests that retinal haemorrhage is a possible complication of infectious mononucleosis in the presence of MOGAD.